Fabrication & Characterization of Hybrid Piezoelectric/Triboelectric Nanocomposite Nanogenerators via Fusion Deposition Modeling - El Toukhy, Khaled (AUC Knowledge Fountain, 2023)
This thesis aims to discuss the potential of using piezoelectric and triboelectric nanogenerators (PTENGs) for energy harvesting, particularly in the sportswear industry. PTENG's main advantage is that it offers good flexibility making it suitable for high-strain applications. The piezoelectric effect is induced by embedding piezoelectric nanofillers into one of the two triboelectric layers. PTENGs can generate both piezoelectric and triboelectric signals when strained resulting in an enhanced output compared to regular piezoelectric nanogenerators (PENGs) and triboelectric nanogenerators (TENGs). TPU was adopted as the matrix for PTENGs advantageous due to their flexibility, low electrical resistivity, and compatibility with additive manufacturing techniques. In this study, a nanocomposite of TPU/ZnO of two different weight percentages (20% ZnO and 15% ZnO) was fabricated using a solution mixing method and subsequently turned into a filament for 3D printing. When applying 5 N, the PENG generated peak potential differences ranging from 3.455 mV to 2630 mV, depending on the weight percentage of ZnO used. Additionally, a cyclic loading test, simulating average walking speed and running, using a layer of 15wt% ZnO/TPU and Ecoflex was done. The surface area of the PTENG and the thickness of the Ecoflex layer varied to test its effect on the performance of the PTENG. The best-performing PTENG under the running cyclic loading resulted in a peak potential difference of 40 V for the piezoelectric response and 67.2 V for the triboelectric response. For the walking test, the best performance was recorded to have a peak potential difference of 22 V and 23.6 V. However, the 20wt% ZnO/TPU layer was not used in the fabrication of the PTENG due to its brittleness causing filament failure or nozzle clogging making it unreliable for long printing hours. These findings highlight the potential of PTENGs in energy harvesting applications, particularly in the sportswear industry, where customized dimensions and enhanced energy harvesting capabilities can be achieved especially in show sole manufacturing which already uses TPU as their go-to material.